Quality of Life and Quality of Care in patients with advanced Chronic Heart Failure (CHF) and advanced Chronic Obstructive Pulmonary Disease (COPD): Implication for Palliative Care from a prospective observational study. (2nd January 2021) - Siouta, N.; Heylen, A.; Aertgeerts, B.; Clement, P.; Janssens, W.; Van Cleemput, J.; Menten, J.
Abstract : Background: Patients with advanced CHF/COPD and their caregivers share many misconceptions about the life-limiting nature of their disease and when compared to cancer patients, CHF/COPD patients are less likely to receive Palliative Care. Aim: This observational prospective study explores (i) the quality of life (QoL) and symptom control and (ii) the quality of care in CHF/COPD patients in an acute hospital setting. Methods: Eligible patients and their informal caregivers filled in (i) the POS questionnaire that assesses the QoL and the symptom control and (ii) the CanHelp Lite questionnaire that assesses quality of care. These questionnaires were completed at inclusion and after a three-month-follow-up. Results: The majority of the participants were 60-79 years old with mild to moderate symptomatology. Older patients or patients with heavy symptoms declined participation. Both patients and caregivers share common and overall positive beliefs concerning patients' QoL and quality of care. Conclusions: The severity of the healthcare condition of the included patients appears to at odds with their positive evaluation of QoL and quality of care. Possible factors contributing to this finding might be the reluctance of physicians to engage to uncomfortable conversations, the patients' denial of "bad-news" and the overall taboo of communication about death.